2004
DOI: 10.1126/science.1104677
|View full text |Cite
|
Sign up to set email alerts
|

Jekyll and Hyde in the Microbial World

Abstract: Fungi are nonmotile organisms that obtain carbon from compounds in their immediate surroundings. Confronted with nutrient limitation, the yeast Saccharomyces cerevisiae undergoes a dimorphic transition, switching from spherical cells to filaments of adherent, elongated cells that can invade the substratum. A complex web of sensing mechanisms and cooperation among signaling networks (including a mitogen-activated protein kinase cascade, cyclic adenosine monophosphate–dependent protein ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Activated Fus3 translocates into the nucleus, relieves repression of the transcriptional activator Ste12, and thereby induces expression of mating-specific genes (48). Likewise, Ste20, Ste11, Ste7, and a different MAPK, Kss1, are needed for the change in budding pattern and elongated morphology necessary for the filamentous growth observed when diploid cells are deprived of nitrogen and for the invasive growth displayed by haploid cells when starved for carbon (59). Activated Kss1 promotes expression of genes under the joint control of Ste12 and another DNA-binding transcription factor, Tec1 (2,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Activated Fus3 translocates into the nucleus, relieves repression of the transcriptional activator Ste12, and thereby induces expression of mating-specific genes (48). Likewise, Ste20, Ste11, Ste7, and a different MAPK, Kss1, are needed for the change in budding pattern and elongated morphology necessary for the filamentous growth observed when diploid cells are deprived of nitrogen and for the invasive growth displayed by haploid cells when starved for carbon (59). Activated Kss1 promotes expression of genes under the joint control of Ste12 and another DNA-binding transcription factor, Tec1 (2,12).…”
mentioning
confidence: 99%
“…Secreted peptides initiate the pheromone response pathway, which prepares cells for mating (60). Invasive growth by haploids and pseudohyphal growth by diploids are triggered when cells are limited for carbon (haploids) or nitrogen (diploids) (59). These three signal transduction pathways have some components in common, in particular, the MAPK kinase kinase (MAPKKK) Ste11.…”
mentioning
confidence: 99%
“…Budding yeast (Saccharomyces cerevisiae) uses MAPK modules to adapt rapidly to environmental changes, such as nutrient limitation (filamentous growth signaling) (84), hyperosmotic stress (high-osmolarity glycerol [HOG] signaling) (91), cell wall damage (Pkc1-dependent signaling) (20), presence of mating-inducing peptides (pheromone signaling) (90), and conditions that evoke meiosis in diploid cells (sporulation) (6,89). Nutrient deprivation triggers a developmental transition from yeast-form (round) cells to cells capable of invasive or pseudohyphal growth (23,63).…”
mentioning
confidence: 99%
“…Pseudohyphal growth under nitrogen source limitation and invasive 1 growth under carbon source limitation involve many of the molecular factors and signaling pathways (for an overview of these pathway components, please refer to the schematic summary of the results of this study shown in Figure 7). In particular, pseudohyphal growth and invasive growth require two classical signaling modalities: (i) a mitogen-activated protein kinase (MAPK) cascade and (ii) 39, 59-cyclic adenosine monophosphate (cAMP) and cAMP-dependent protein kinase A (PKA) (Lengeler et al 2000;Pan et al 2000;Truckses et al 2004). The MAPK cascade that promotes FG consists of Ste20 (PAK/MAPKKKK), Ste11 (MAPKKK), Ste7 (MAPKK), and Kss1 (MAPK).…”
mentioning
confidence: 99%
“…External nutrient supply affects the division pattern, adhesivity, and morphology of cells and the colonies of the budding yeast Saccharomyces cerevisiae (Gancedo 2001;Gagiano et al 2002;Palecek et al 2002;Schneper et al 2004;Truckses et al 2004;Verstrepen and Klis 2006;Chen and Thorner 2007;Granek and Magwene 2010). During conditions of nutrient sufficiency, cells are ovoid, and haploid cells bud to form daughter cells at the cell pole corresponding to their own birth site (an ''axial'' budding pattern), whereas diploid cells bud alternately from their birth end and from the opposite cell pole (a ''bipolar'' budding pattern).…”
mentioning
confidence: 99%